I. OVERVIEW OF THE METHODOLOGY OF TRANSITION METAL SUBSTITUTION KINETICS. II. SPECTROPHOTOMETRIC INVESTIGATION OF THE EXTENT OF ION-PAIRING BETWEEN AQUOPENTAAMMINERHODIUM(III) AND CHLORIDE IN ACIDIC AQUEOUS SOLUTION. III. THE SYNTHESIS OF TRANS-DIAQUOBIS(ETHYLENEDIAMINE)IRIDIUM(III). IV. THE KINETICS OF THE ANATION BY CHLORIDE OF TRANS-DIAQUOBIS(ETHYLENEDIAMINE)RHODIUM(III) IN ACIDIC AQUEOUS SOLUTION. - Pfaff, Robert C. (My University, 1980)
The work reported here is part of an effort to develop a new method for studying the kinetics of transition metal substitution reactions. In the past, reactions have been studied at high, constant ionic strength following from the assumption that this maintains constant values of the activity coefficients. This assumption has been shown to be invalid. In the novel approach, no substitutionally inert salt is added to maintain a constant ionic strength necessitating the calculation of activity coefficients and the inclusion of them in all kinetic expressions. In order to establish the validity of the novel approach, a course of study was initiated. The results of the studies of two reactions are reported. The reaction of aquopentaamminerhodium(III) with chloride proceeds via an interchange mechanism as determined from the results of batch kinetic, potentiometric ion-pairing, and spectrophotometric ion-pairing experiments. The novel method yielded values which compare well with those given by the traditional approach but allows resolution of the parameters instead of the composite constants yielded by the traditional approach. The reaction of trans-diaquobis(ethylenediamine)rhodium(III) with chloride proceeds via the dissociative mechanism. The values of the kinetic parameters obtained agree well with those from traditional experiments. In this reaction, resolution of the parameters was not possible due to the complexity of the system but the novel approach outperformed the traditional method. The attempted synthesis of trans-diaquobis(ethylenediamine)iridium(III) is also discussed.
The kinetics of the anation by chloride of trans-diaquobis(ethylenediamine)rhodium(III) in acidic aqueous solution.
Spectrophotometric investigation of the extent of ion-pairing between aquopentaamminerhodium(III) and chloride in acidic aqueous solution.
Keywords: Chemistry, Inorganic.